2016
DOI: 10.1128/jvi.01042-16
|View full text |Cite
|
Sign up to set email alerts
|

Protein Primary Structure of the Vaccinia Virion at Increased Resolution

Abstract: Here we examine the protein covalent structure of the vaccinia virus virion. Within two virion preparations, >88% of the theoretical vaccinia virus-encoded proteome was detected with high confidence, including the first detection of products from 27 open reading frames (ORFs) previously designated "predicted," "uncharacterized," "inferred," or "hypothetical" polypeptides containing as few as 39 amino acids (aa) and six proteins whose detection required nontryptic proteolysis. We also detected the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(56 citation statements)
references
References 70 publications
6
50
0
Order By: Relevance
“…The data set presented is the largest intrinsic virus signaling network uncovered to date. Consistent with other studies 30,53 sequence alignment of 15 unambiguous sites provided no clear consensus for F10 or H1 substrate recognition ( Supplementary Fig. 5), suggesting that other (e.g.…”
Section: Revealing the F10/h1 Viral Signaling Networksupporting
confidence: 90%
“…The data set presented is the largest intrinsic virus signaling network uncovered to date. Consistent with other studies 30,53 sequence alignment of 15 unambiguous sites provided no clear consensus for F10 or H1 substrate recognition ( Supplementary Fig. 5), suggesting that other (e.g.…”
Section: Revealing the F10/h1 Viral Signaling Networksupporting
confidence: 90%
“…The association of I2 with purified virus particles was previously shown by Western blotting using an epitope tag antibody (9) and by mass spectroscopy (4,6). We were interested in determining its intracellular localization since this might help to further investigate its role.…”
Section: Resultsmentioning
confidence: 99%
“…The I2 protein is predicted to have 72 amino acids with a calculated mass of 8.4 kDa and a C-terminal TM domain. The protein is synthesized following viral DNA replication and is associated with purified MVs (6,9). Using a recombinant VACV with a tetracycline-inducible I2L ORF, Nichols et al (9) showed that repression of I2L results in a profound reduction in virion infectivity due to the inability of the virions to enter cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3). In the virion-packaged form of RP30, this Pro/Ser-rich tail was recently shown to be highly phosphorylated (112). It remains to be proven whether phosphorylation modulates a switch between RP30's two functions specifically in the Poxviridae.…”
Section: Tfiismentioning
confidence: 99%